Efektivitas teori psikologi gestalt pada pembelajaran usia remaja - Kamila, Bintana Cahya; Lestari, Denia Septi Dwi; Raniadi, Divani (Universitas Indraprasta PGRI, 2023)
gestalt psychology is a psychology that studies all scenes or phenomena that are oriented towards the whole and unity of each data. This psychology has a variety of objects for its application, both individuals from infancy to the elderly. Each age grouping of individuals has its own unique characteristics to be applied with gestalt psychology. For example, individuals in adolescence. Adolescence is a time when an individual experiences significant physical and mental growth. Therefore, this paper aims to discuss the definition, characteristics of adolescents, and its application as evidence of the effectiveness of gestalt psychology theory in adolescent learning.